Do self-assessments of health predict future mortality in rural South Africa?: the case of KwaZulu-Natal in the era of antiretroviral treatment - Olgiati, Analia; Bärnighausen, Till; Newell, Marie-Louise (Tropical medicine & international health, 2012)
Objectives: While self-assessments of health (SAH) are widely employed in epidemiological studies, most of the evidence on the power of SAH to predict future mortality originates in the developed world. With the HIV pandemic affecting largely prime age individuals, the strong association between SAH and mortality derived from previous work might not be relevant for the younger at-risk groups in countries with high HIV prevalence in the era of antiretroviral treatment. We investigate the power of SAH to predict mortality in a community with high HIV prevalence and antiretroviral treatment (ART) coverage using linked data from three sources: a longitudinal demographic surveillance, one of Africa’s largest, longitudinal, population-based HIV surveillances, and a decentralised rural HIV treatment and care programme. Methods  We used a Cox proportional hazards specification to examine whether SAH significantly predicts mortality hazard in a sample composed of 9217 adults aged 15-54, who were followed up for mortality for 8 years. Results  Self-assessments of health strongly predicted mortality (within 4 years of follow-up), with a clear gradient of the adjusted hazard ratios (aHRs), relative to the baseline of ‘excellent’ self-assessed health status and controlling for age, gender, marital status, the socio-economic status (SES), variables education, employment, household expenditures and household assets, and HIV status and ART uptake: 1.40 (95% CI 0.99-1.96) for ‘very good’ self-assessed health status (SAHS); 2.10 (95% CI 1.52-2.90) for ‘good’ SAHS; 3.12 (95% CI 2.18-4.45) for ‘fair’ SAHS; and 4.64 (95% CI 2.93-7.35) for ‘poor’ SAHS. While a similar association remained in the unadjusted analysis of long-term mortality (within 4-8 years of follow-up) the hazard ratios capturing SAH are jointly insignificant in predicting of mortality once HIV status, ART uptake and gender, age, marital status and SES were controlled for. HIV status and ART programme participation were large and highly significant predictors of long-term mortality. Conclusions  Our findings validate SAH as a variable that significantly predicts short-term mortality in a community in sub-Saharan Africa with high HIV prevalence, morbidity and mortality. When predicting long-term mortality, however, it is much more important to know a person's HIV status and ART programme participation than SAH.